2018
DOI: 10.1155/2018/9412167
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity and Acute Oral Toxicity Test for Herbal Poultry Feed Supplements

Abstract: Herbal products are being used and trusted globally for thousands of years for their health benefits and limited side effects. Globally, a general belief amongst the consumers is that herbal supplements are always safe because they are “natural.” But later, research reveals that they may not be safe. This raises concern on their safety and implications for their use as feed supplement or medicine. Toxicity testing can reveal some of the risks that may be associated with use of herbs, therefore avoiding potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…So concern related to the safety of medicinal plants is becoming one of the emerging interests for researchers and the investigation of toxic aspects of herbs that might be associated with their usage, therefore, avoiding potential harmful effects. 50 The results of cytotoxic activity suggested that the selected medicinal plant has significant ( P <.05) membrane-stabilizing (antihemolytic) potential. The safety of W. somnifera regarding toxicity, side effects and dosing is not yet well established, so the current study was the first time to explore the in vitro cytotoxic potential.…”
Section: Discussionmentioning
confidence: 99%
“…So concern related to the safety of medicinal plants is becoming one of the emerging interests for researchers and the investigation of toxic aspects of herbs that might be associated with their usage, therefore, avoiding potential harmful effects. 50 The results of cytotoxic activity suggested that the selected medicinal plant has significant ( P <.05) membrane-stabilizing (antihemolytic) potential. The safety of W. somnifera regarding toxicity, side effects and dosing is not yet well established, so the current study was the first time to explore the in vitro cytotoxic potential.…”
Section: Discussionmentioning
confidence: 99%
“… 26 The concern related to the safety of medicinal plants is becoming one of the emerging interests for researchers and the investigation of toxic aspects of herbs that might be associated with their usage, therefore avoiding potential harmful effects. 27 The results of mutagenicity test explored that selected medicinal plant did not possess mutagenic activity or in other words selected natural herb is non-mutagenic in nature. According to literature review, this was the first time that selected medicinal plant was screened out for the mutagenic activities.…”
Section: Discussionmentioning
confidence: 99%